The Use of Cefiderocol as Salvage Therapy in an Infant Receiving ECMO and Continuous Renal Replacement Therapy - Stefania Mercadante; Costanza Tripiciano; Lorenza Romani; Matteo Di Nardo; Gabriella Bottari; Bianca Maria Goffredo; Raffaele Simeoli; Isabella Guzzo; Laura Lancella; Charalampos Antachopoulos; Maia De Luca (Antibiotics, 2023)
Background: Infections caused by antimicrobial-resistant (AMR) pathogens are increasing worldwide, representing a serious global public health issue with high morbidity and mortality rates The treatment of Pseudomonas aeruginosa (PA) infections has become a significant challenge due to its ability to develop resistance to many of the currently available antibiotics, especially in intensive care unit (ICU) settings. Among the very few therapeutic lines available against extensively drug-resistant (XDR)-PA and/or with difficult-to-treat resistance (DTR)-PA, cefiderocol is an injectable siderophore cephalosporin not licensed for use in pediatric patients. There are only a few case reports and two ongoing trials describing the administration of this cephalosporin in infants. Case presentation: This report describes the case of a critically ill 8-month-old girl affected by ventilator-associated pneumonia (VAP) infection complicated by bloodstream infection (BSI) sustained by VIM-producing PA. She was treated with cefiderocol as a salvage therapy during ECMO and CRRT support. Conclusions: In healthcare settings, treating multidrug-resistant, Gram-negative bacteria poses a serious challenge, especially in pediatric patients. Our findings suggest that cefiderocol can be considered as an off-label rescue therapy in selected pediatric cases.